2021
DOI: 10.1101/2021.01.18.427054
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural and functional characterization of a putativede novogene inDrosophila

Abstract: Comparative genomic studies have repeatedly shown that new protein-coding genes can emerge de novo from non-coding DNA. Still unknown is how and when the structures of encoded de novo proteins emerge and evolve. Combining biochemical, genetic and evolutionary analyses, we elucidate the function and structure of goddard, a gene which appears to have evolved de novo at least 50 million years ago within the Drosophila genus.Previous studies found that goddard is required for male fertility. Here, we show that God… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 92 publications
1
15
0
Order By: Relevance
“…We showed previously that the putative de novo gene saturn is required for maximal sperm production, as well as for the ability of transferred sperm to migrate successfully to sperm storage organs in females (Gubala et al 2017). Another putative de novo gene, goddard, is required for sperm production and encodes a cytoplasmic protein that appears to localize to elongating axonemes (Gubala et al 2017;Lange et al 2021). Loss of goddard impairs the individualization of spermatid bundles (Lange et al 2021), thus exerting an effect that appears to be upstream of those observed for saturn and atlas.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We showed previously that the putative de novo gene saturn is required for maximal sperm production, as well as for the ability of transferred sperm to migrate successfully to sperm storage organs in females (Gubala et al 2017). Another putative de novo gene, goddard, is required for sperm production and encodes a cytoplasmic protein that appears to localize to elongating axonemes (Gubala et al 2017;Lange et al 2021). Loss of goddard impairs the individualization of spermatid bundles (Lange et al 2021), thus exerting an effect that appears to be upstream of those observed for saturn and atlas.…”
Section: Discussionmentioning
confidence: 99%
“…Another putative de novo gene, goddard, is required for sperm production and encodes a cytoplasmic protein that appears to localize to elongating axonemes (Gubala et al 2017;Lange et al 2021). Loss of goddard impairs the individualization of spermatid bundles (Lange et al 2021), thus exerting an effect that appears to be upstream of those observed for saturn and atlas. Here, we report another novel function for a putative de novo gene: encoding an essential transition protein that is necessary for proper nuclear condensation in spermiogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations